1970
DOI: 10.1097/00004032-197006000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Accidental Personnel Exposure to Plutonium-238

Abstract: An explosion inside a 238Pu glove box line at iMound Laboratory resulted in significant inhalation exposures being received by three personnel. The three employees were sent to the Dow Chemical Company's Rocky Flats site for whole body counting three weeks after the incident. Whole body counting measurements were made using the 17 keV (Average) X-ray associated with the decay of 238Pu. These measurements indicated that the employees had lung burdens of 0.134 pCi, 0.141 pCi, and 0.091 pCi.The urine data obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A number of historical studies have shown that the physicochemical properties of plutonium oxide particles can vary depending on the source and history of the material (Anderson et al 1970;Ramsden et al 1970;Newton et al 1983;Carbaugh et al 1991;Guilmette et al 1994;Hickman et al 1995). Lung scans were taken to measure initial lung burden (Anderson et al 1970;Newton et al 1983;Carbaugh et al 1991), and bioassay samples were taken from the exposed workers to assess the excretion rates of plutonium from the body and to estimate lung burden and radiation dose based on an assumed dissolution rate of plutonium aerosols (Anderson et al 1970;Ramsden et al 1970;Newton et al 1983;Carbaugh et al 1991;Guilmette et al 1994;Hickman et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of historical studies have shown that the physicochemical properties of plutonium oxide particles can vary depending on the source and history of the material (Anderson et al 1970;Ramsden et al 1970;Newton et al 1983;Carbaugh et al 1991;Guilmette et al 1994;Hickman et al 1995). Lung scans were taken to measure initial lung burden (Anderson et al 1970;Newton et al 1983;Carbaugh et al 1991), and bioassay samples were taken from the exposed workers to assess the excretion rates of plutonium from the body and to estimate lung burden and radiation dose based on an assumed dissolution rate of plutonium aerosols (Anderson et al 1970;Ramsden et al 1970;Newton et al 1983;Carbaugh et al 1991;Guilmette et al 1994;Hickman et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Lung scans were taken to measure initial lung burden (Anderson et al 1970;Newton et al 1983;Carbaugh et al 1991), and bioassay samples were taken from the exposed workers to assess the excretion rates of plutonium from the body and to estimate lung burden and radiation dose based on an assumed dissolution rate of plutonium aerosols (Anderson et al 1970;Ramsden et al 1970;Newton et al 1983;Carbaugh et al 1991;Guilmette et al 1994;Hickman et al 1995). In one case, samples were taken for a solubility test (Anderson et al 1970), and in another case, airborne filter or personal samples were taken for measurement of activity concentration and particle size distribution (Ramsden et al 1970).…”
Section: Introductionmentioning
confidence: 99%
“…’ The concept was not new in 1977. For example, Anderson et al. (1970) noted that part of the rapid urinary excretion observed after accidental inhalation of 238 Pu was: ‘thought to be due to refractory particles of colloidal dimensions which were transferred very rapidly to the systemic system …’. (789) As described above, high-fired 239 Pu dioxide particles dissolve extremely slowly in the lungs, although a small fraction of ILD, usually <1%, is absorbed rapidly.…”
Section: Plutonium (Z = 94)mentioning
confidence: 99%
“…’ The concept was not new in 1977. For example, Anderson et al. (1970) noted that part of the rapid urinary excretion observed after accidental inhalation of 238 Pu was: ‘thought to be due to refractory particles of colloidal dimensions which were transferred very rapidly to the systemic system …’.…”
Section: Plutonium (Z = 94)mentioning
confidence: 99%